2023
DOI: 10.1038/s41559-023-02093-x
|View full text |Cite
|
Sign up to set email alerts
|

Biome-scale temperature sensitivity of ecosystem respiration revealed by atmospheric CO2 observations

Abstract: The temperature sensitivity of ecosystem respiration regulates how the terrestrial carbon sink responds to a warming climate but has been difficult to constrain observationally beyond the plot scale. Here we use observations of atmospheric CO2 concentrations from a network of towers together with carbon flux estimates from state-of-the-art terrestrial biosphere models to characterize the temperature sensitivity of ecosystem respiration, as represented by the Arrhenius activation energy, over various North Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 113 publications
0
0
0
Order By: Relevance
“…Mean annual temperatures in the peatland increased by 1°since the early 1960ies and maximum temperatures by 8°C for instance. Knowing the sensitivity of ecosystem respiration to temperature (Ben & Thompson, 2010;Sun et al, 2023), it is likely that the ER increased in the last 50 years. It has been observed that drier conditions in summer were associated with lower carbon uptake in Canadian boreal peatlands (McDonald et al, 2023).…”
Section: Temperate Mountain Peatlands: From Weak Carbon Sinks To Pote...mentioning
confidence: 99%
“…Mean annual temperatures in the peatland increased by 1°since the early 1960ies and maximum temperatures by 8°C for instance. Knowing the sensitivity of ecosystem respiration to temperature (Ben & Thompson, 2010;Sun et al, 2023), it is likely that the ER increased in the last 50 years. It has been observed that drier conditions in summer were associated with lower carbon uptake in Canadian boreal peatlands (McDonald et al, 2023).…”
Section: Temperate Mountain Peatlands: From Weak Carbon Sinks To Pote...mentioning
confidence: 99%
“…Although we lack the observations to verify this, we hypothesise the GPP response is dominated by the atmospheric stress through VPD, while the soil moisture limitation that would also affect TER is smaller. Biosphere models vary strongly in simulations of such a TER response (Clark et al, 2011;Haynes et al, 2020;Peters et al, 2018) and recent work suggests a general overestimate of temperature sensitivity (Sun et al, 2023). The good correspondence to atmospheric data nevertheless indicates a good NEE drought response in SiB4 which, together with a reasonable response in GPP, also suggests a reasonable TER response of SiB4.…”
Section: Discussionmentioning
confidence: 85%
“…The GPP impact on atmospheric CO 2 is typically larger and more variable than that of TER in summer (Piao et al, 2020;Tolk et al, 2009).Our study nevertheless suggests also a role of TER and soil moisture in the drought response, as we find a strong reduction of GPP which, according to the atmospheric CO 2 mole fraction constraints, does not fully balance observed NEE reductions without also considering a TER reduction. However, contrary to GPP, which can be estimated from satellite products, TER cannot currently be quantified on a large scale (although recently advances in the quantification of the temperature sensitivity of TER have been made (Sun et al, 2023))). Locally, our EC observations indeed show reduced TER and reduced GPP due to the drought in the 4 4 99…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation